Serum Trefoil Factor 3 in Endometrioid Endometrial Carcinoma: Exploratory Diagnostic Value and Association with Lymphovascular Space Invasion - Bilgesu Çetinel Kaygun; Varol Gülseren; Merve Özel Yetkin; Ertuğrul Şen; Gülden Başkol; Fulya Çağlı; Terlan Selin Kotan; İbrahim Serdar Serin; Bülent Özçelik; Kemal Güngördük (Journal of Clinical Medicine, 2026)
Objectives: The primary objective of this exploratory study was to compare serum Trefoil factor family 3 (TFF3) levels among patients with grade 1–2 endometrioid endometrial cancer (EC), leiomyoma distorting the endometrial cavity, and healthy controls, and to explore the cross-sectional association between serum TFF3 and lymphovascular space invasion (LVSI) in EC. Methods: The prospective observational case–control study comprised three groups. The first group consisted of all grade I–II endometrioid-type EC patients who underwent hysterectomy at our institution. The second group comprised patients with leiomyoma causing compression in the endometrial cavity who also underwent hysterectomy. Patients with histopathological evidence of myoma after hysterectomy were included in the study. All patients who visited between January 2023 and January 2024 were enrolled in the first two groups. The third control group involved patients with normal findings on sonographic assessment who attended annual gynecological follow-up visits. Results: One hundred thirteen patients were enrolled in the study. Mean preoperative TFF3 levels were significantly higher in both EC and leiomyoma groups compared with controls, whereas EC and leiomyoma did not differ. Serum TFF3 decreased significantly on the first postoperative day in the EC group, whereas no significant change was observed in the leiomyoma group. Within the EC group, an exploratory comparison showed a significantly higher average TFF3 value in cases with lymphovascular space invasion (LVSI). Conclusions: Serum TFF3 is elevated in both benign and malignant pathologies involving the endometrial cavity and shows limited specificity for distinguishing EC from leiomyoma. The observed association with LVSI is preliminary and hypothesis-generating; larger, adequately powered studies are required before any diagnostic or prognostic role can be established.